Infantile hemangioma - Kurzeja, Marta; Pawlik, Katarzyna; Sienicka, Agnieszka; Olszewska, Małgorzata; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2022)
Infantile hemangiomas are the most common vascular tumors of infancy. They usually appear within the first few weeks after birth and undergo regression over time, usually by the age of four. They are more common in girls, Caucasians, twins, infants born preterm or with a low birth weight. The pathogenesis of hemangiomas remains not fully understood. Infantile hemangiomas can be classified based on their depth and anatomical configuration. Superficial hemangiomas appear as a red macule or patch, while deep hemangiomas appear as a bluish papule or nodule. In most cases the diagnosis is based on the clinical picture. The differential diagnosis includes vascular anomalies, pyogenic granuloma or Kaposiform hemangioendothelioma. In most cases, infantile hemangiomas do not require any treatment. Only 10–20% of cases need to be treated because of complications. Propranolol administered orally is the treatment of choice.